Radioembolisation with Y90-resin microspheres followed by nivolumab for advanced hepatocellular carcinoma (CA 209-678): a single arm, single centre, phase 2 trial. (December 2021) - Tai, David; Loke, Kelvin; Gogna, Apoorva; Kaya, Neslihan Arife; Tan, Sze Huey; Hennedige, Tiffany; Ng, David; Irani, Farah; Lee, Joycelyn; Lim, Jia Qi; Too, Chow Wei; Ng, Matthew C H; et al.
Summary: Background: Therapeutic synergism between radiotherapy and immune checkpoint blockade has been observed in preclinical models of hepatocellular carcinoma. We aimed to study the safety and efficacy of sequential radioembolisation with yttrium-90-resin microspheres (Y90-radioembolisation) followed by nivolumab in patients with advanced hepatocellular carcinoma. Methods: Patients with Child-Pugh A cirrhosis and advanced hepatocellular carcinoma not suitable for curative surgery were treated with Y90-radioembolisation followed by intravenous nivolumab 240 mg 21 days after Y90-radioembolisation and every 2 weeks thereafter. The primary endpoint, assessed in the per-protocol population, was the objective response rate, determined by RECIST version 1.1, defined as the proportion of patients with a confirmed complete or partial response observed for lesions both within and outside the Y90-radioembolisation field. This study is registered with ClinicalTrials.gov, NCT03033446 and has been completed. Findings: 40 patients were enrolled, of whom 36 received Y90-radioembolisation followed by nivolumab. One (3%) patient had a complete response and ten (28%) had a partial response; the objective response rate was 30·6% (95% CI 16·4–48·1). The most common treatment-related adverse events of any grade were pruritus (18 [50%] of 36 patients) and maculopapular rash (13 [36%]). Two (6%) patients experienced grade 3–4 treatment-related adverse events: one patient had a grade 3 increase in alanine aminotransferase levels, grade 3 bilirubin increase, and grade 4 increase in aspartate aminotransferase levels, while the other had a grade 3 maculopapular rash. Five (14%) patients had a treatment-related serious adverse event (Steven-Johnson syndrome, hepatitis E infection, fever, liver abscesses, and ascites). Interpretation: Y90-radioembolisation followed by nivolumab resulted in an encouraging objective response rate in patients with advanced hepatocellular carcinoma, although the activity observed was not as high as the study was powered for. This strategy should be further evaluated in patients with Barcelona Clinic Liver Clinic (BCLC) stage B hepatocellular carcinoma that is ineligible or refractory to transarterial chemoembolisation and patients with BCLC C disease without extrahepatic spread. Funding: National Medical Research Council Singapore, Bristol-Myers Squibb, Sirtex.